PERANCANGAN ELECTRONIC COMMERCE BERBASIS B2C PADA TOKO ATK SINDORO - Dedi Irawan; Muhammad Junaidi; Yoeyong Rahsel; Taufik Udin (LPPM STMIK Pringsewu, 2017)
Trade through the internet network is known as electronic commerce has advantages that directly can be useful for Atk Sindoro one that uses the internet to aim to expand the marketing and service through the Internet so as to add value to the Ats Sindoro Shop. In order to customer is done by contacting by phone or go to company, so that takes a long time and hamper customer in doing transaction. Therefore this thesis is made aiming to design a web application program that is used for online ordering activities at Atk Sindoro. This research uses RUP methodology, programming language and database used in making this system is PHP and MySQL. With this system facilitate the process of sale and transaction of consumer ordering.